A framework to assess cultural safety in Australian public policy. (22nd February 2019) - Mackean, Tamara; Fisher, Matthew; Friel, Sharon; Baum, Frances
Abstract: The concept of cultural safety (CS) has been developed as a critical perspective on healthcare provided to Indigenous service users in neo-colonial countries such as New Zealand, Australia and Canada. Unlike other frameworks for culturally competent healthcare, a CS approach recognizes impacts of colonization and power inequalities on Indigenous peoples and asks how these may manifest in healthcare settings. It has been argued that CS thinking is suited to critical analysis of public policy, but there has been limited work in this direction. Drawing on literature on CS in Australian healthcare, we defined a CS framework consisting of five concepts: reflexivity, dialogue, reducing power differences, decolonization and regardful care. Our research examined whether and in what terms this framework could be adapted as a tool for critical analysis of Australian public policy as it affects Aboriginal and Torres Strait Islander peoples. We used a collaborative inquiry process combining perspectives of an Aboriginal researcher and a non-Indigenous researcher. We developed a thematic analysis framework to examine how the five concepts might be reflected in contemporary writings on policy by leading Aboriginal or Torres Strait Islander thinkers. We found the framework is applicable as a tool for policy analysis; bringing together key concerns raised by Aboriginal and Torres Strait Islander leaders and critical concepts such as sovereignty and interface thinking. We concluded the framework is likely to be a useful tool for critical, systemic thinking about public policy as it affects Indigenous peoples and for specifying areas where performance can be improved to achieve culturally safe policy.